LIRO – EPIKALÍQ SHÍǴARMALARDA KÓRKEM SÚWRETLEW QURALLARÍ HÁM USILLARÍ - Qaniyazova, F.A. (SCIENCE and SOCIETY, 2021)
In this article, we have focused on the specifics of ballads in Karakalpak literature related to the issue of literary language. We have analyzed the influence of literary language on content, form, and its importance in description. Consequently, the literary language of ballads is a very rich genre. We think that this topic requires special research.
Keywords: ballad; trop; lyro-epic; metaphor; epithet; antithesis; hyperbole